A New Golden Age for Computer Architecture. - HENNESSY, JOHN L.; PATTERSON, DAVID A. (Communications of the ACM, 2019)
The article examines the relationship between computer software and architecture and discusses how innovations in software can influence architectural advancement. Particular attention is given to improvements in the hardware/software interface.